Lithuanian Nicknames Referring to Person’s Location, Geographic Origin and Visitation - Butkus, Alvydas (Kalbotyra, 1988)
Such motives as location, geographic origin and visitation belong to a periphery of motivation of modern Lithuanian nicknames.There are about 4.2% of the nicknames referring to person’s location. The nicknames point to nature object near /or in/ a person’s farm-stead as well as a farm-stead’s place in a village. Sometimes the essential feature of building is also pointed out. Most of the nicknames are derivatives made by means of suffixation, especially adding the suffix -inis: Berižinis /: beržas ‘birch-tree’/, Galinis /: galas ‘edge’, the most frequent Lithuanian nickname/, Lentinis, /: lenta ‘board’/.One per cent of modern Lithuanian nicknames refer to person’s geographic origin / nicknames Naujēlis, Šviēžikas, Dzū̄kas etc. / and 0.6% to visitation / nickname Amerikōnas, Raseīčikas, Rygēčius, etc. /.